MULTIPHASE SPECTROSCOPIC OBSERVATIONS OF THE LONG-PERIOD CEPHEIDS l CARINAE - Usenko, I. A.; Kravtsov, V. V.; Kovtyukh, V. V.; Berdnikov, L. N.; Knyazev, A. Yu.; Chini, R.; Fokin, A. B. (Одеські астрономічні публікації, 2013)
Thirty three spectra (one spectrum for the each of 33 observational nights) have been performed to coverall pulsational period of the 35.5-days Cepheid l Car. Due to these data we have obtained for the ﬁrst time the detailed curves of effective temperature, gravity and turbulent velocity. Curves of gravity and turbulent velocity show complicated changes, connected probably with dynamics of extensive Cepheid’s atmosphere. The mean atmosphere parameters of l Car are: Teff =4984±15K; log g = 1.13; Vt =6.67kms−1. Having a solar metallicity [Fe/H]=+0.02dex, this Cepheid demonstrate sudden results for the ”key” elements abundances of yellow supergiants evolution, – all they are close to the solar ones. In this case l Car resembles to SV Vul, – Cepheid with 45-days pulsational period and nearly like spectral type. It is possible that l Car is an object crossing the Cepheids instability strip for the ﬁrst time. The content of other elements is close to solar one too.